Prediction of early hepatocellular carcinoma recurrence using germinal center kinase-like kinase - Ho, Cheng-Hsun (Oncotarget, 2016)
Germinal center kinase-like kinase (GLK) is a key controller of autoimmunity. In this study, we assessed the clinical relevance and tumorigenic effects of GLK in hepatocellular carcinoma (HCC). Using immunohistochemistry, we showed that the GLK proportion score increased in both cancerous and adjacent non-cancerous liver tissue from patients with HCC recurrence. A Kaplan-Meier analysis revealed that patients with a wide distribution of GLK in non-cancerous liver tissue had a higher rate of HCC recurrence than those with very low or no GLK expression. Multivariate Cox regression analyses indicated that a high GLK proportion score in non-cancerous liver tissue was an independent predictor of early HCC recurrence after resection. Lentiviral vector-mediated overexpression of GLK activated the nuclear factor kappa B (NFκB) signaling cascade and accelerated cell cycle progression in primary human hepatocytes, thereby promoting proliferation. An increase in GLK expression coincided with NFκB activation and enhanced expression of proliferating cell nuclear antigen in HCC tissue. Our findings demonstrate a potential hepatocarcinogenic effect of GLK and the feasibility of using GLK to predict early HCC recurrence.